"Abnormal" Addition of NHC to a Conjugate Acid of CAAC: Formation of N‐Alkyl‐Substituted CAAC2. Issue 48 (23rd July 2018) - Mandal, Debdeep; Dolai, Ramapada; Kalita, Pankaj; Narayanan, Ramakirushnan Suriya; Kumar, Ravi; Sobottka, Sebastian; Sarkar, Biprajit; Rajaraman, Gopalan; Chandrasekhar, Vadapalli; Jana, Anukul
Abstract: The addition reactions of N‐heterocyclic carbenes (NHCs) are mostly known to occur through the carbenic centre (C2), which leads to a "normal" adduct. Herein, we report the "abnormal" addition of NHC Dip 1 (1, 3‐(2, 6‐ i Pr2 C6 H3 )‐imidazole‐2‐ylidene) to a conjugate acid of cyclic (alkyl)(amino)carbene2 (CAAC i Pr =1‐ i Pr‐3, 3, 5, 5‐Me4 ‐pyrrolinium triflate). Mechanistic study revealed that this reaction proceeded through the in situ formation of 1, 3‐(2, 6‐ i Pr2 C6 H3 )‐imidazolium cation4 and N‐i Pr‐substituted CAAC5 followed by the oxidative addition of compound5 across the C4−H bond (alias backbone C−H) of compound4 . The in situ formation of compound5 was also proven by the oxidative addition of it to the N−H group of i PrNH2 . DFT calculations also supported the mechanistic findings. A different methodology for the in situ generation of compound5 by using TMPLi is also described. Abstract : Backbone‐functionalized N‐heterocyclic carbenes : The abnormal addition of N‐heterocyclic carbene (NHC)1 to the conjugated acid of a cyclic(alkyl)(amino)carbene (CAAC)2 is reported (see scheme). The mechanistic study shows that the reaction proceeds through an acid–base reaction by the formation of compound4, a conjugated acid of NHC1, and N ‐alkyl‐substituted CAAC5 .